Cultivating Innovative Work Behavior of Nurses Through Diversity Climate: The Mediating Role of Job Crafting - Lubaina D. Baig; Malik F. Azeem; Adil Paracha (SAGE Publishing, 2022)
Introduction Innovative work behavior of nurses is essential to deliver affordable quality healthcare services. Diversity climate and job crafting are a few of the supportive managerial strategies that can be applied to cultivate the innovative capacity of nurses. Objective Aim for the current study is to: (a) examine the role of diversity climate in cultivating innovative work behavior of nurses directly; and (b) indirectly through job crafting. Methods For this study data was collected through cross-sectional design employing simple random sampling using structured questionnaires from 283 nurses. Data was analyzed using SPSS.Amos.21. Results Results revealed the positive influence of diversity climate on innovative work behavior directly (γ = 0.51, p  < .001) and indirectly through job crafting (ρ = 0.235, p  < .001). Conclusion The current study revealed that diversity climate significantly influences the innovative work behavior of employees directly and indirectly through Job crafting. Healthcare management can integrate diversity management policies and job crafting techniques in their strategies to foster innovative work behavior of nurses.